Psychology of hate - Lockhardt, Carol T. (Psychology of emotions, motivations, and actions series., 2010)
Hate seems to be an emotion that won't go away. It is seen in the interactions between humans on a daily basis - on television, on the streets and in conversations around the world. "Psychology of Hate" presents original analyses of hate from different perspectives including its manifestations in crime and personal relations. -- Product Description.